Global Respiratory Syncytial Virus–Related Infant Community Deaths. (2nd September 2021) - Mazur, Natalie I; Löwensteyn, Yvette N; Willemsen, Joukje E; Gill, Christopher J; Forman, Leah; Mwananyanda, Lawrence M; Blau, Dianna M; Breiman, Robert F; Madhi, Shabir A; Mahtab, Sana; Gurley, Emily S; El Arifeen, Shams; et al.
Abstract: Background: Respiratory syncytial virus (RSV) is a leading cause of pediatric death, with >99% of mortality occurring in low- and lower middle-income countries. At least half of RSV-related deaths are estimated to occur in the community, but clinical characteristics of this group of children remain poorly characterized. Methods: The RSV Global Online Mortality Database (RSV GOLD), a global registry of under-5 children who have died with RSV-related illness, describes clinical characteristics of children dying of RSV through global data sharing. RSV GOLD acts as a collaborative platform for global deaths, including community mortality studies described in this supplement. We aimed to compare the age distribution of infant deaths <6 months occurring in the community with in-hospital. Results: We studied 829 RSV-related deaths <1 year of age from 38 developing countries, including 166 community deaths from 12 countries. There were 629 deaths that occurred <6 months, of which 156 (25%) occurred in the community. Among infants who died before 6 months of age, median age at death in the community (1.5 months; IQR: 0.8−3.3) was lower than in-hospital (2.4 months; IQR: 1.5−4.0; P  < .0001). The proportion of neonatal deaths was higher in the community (29%, 46/156) than in-hospital (12%, 57/473, P  < 0.0001). Conclusions: We observed that children in the community die at a younger age. We expect that maternal vaccination or immunoprophylaxis against RSV will have a larger impact on RSV-related mortality in the community than in-hospital. This case series of RSV-related community deaths, made possible through global data sharing, allowed us to assess the potential impact of future RSV vaccines. Abstract : The global age distribution of RSV-related deaths in the community is unknown. Children dying of RSV in the community are younger than children dying in-hospital in developing countries. We expect the impact of RSV prevention via maternal vaccination or monoclonal antibody prophylaxis on mortality in early life to be higher for community than in-hospital RSV-related deaths.